Bright exciton fine-structure in two-dimensional lead halide perovskites - Do, Thi Thu Ha (2022)
The fast-growing field of atomically thin semiconductors urges a new understanding of two-dimensional excitons, which entirely determine their optical responses. Here, taking layered lead halide perovskites as an example of unconventional two-dimensional semiconductors, by means of versatile optical spectroscopy measurements, we resolve fine-structure splitting of bright excitons of up to ∼2 meV, which is among the largest values in two-dimensional semiconducting systems. The large fine-structure splitting is attributed to the strong electron-hole exchange interaction in layered perovskites, which is proven by the optical emission in high magnetic fields of up to 30 T. Furthermore, we determine the g-factors for these bright excitons as ∼+1.8. Our findings suggest layered lead halide perovskites are an ideal platform for studying exciton spin-physics in atomically thin semiconductors that will pave the way toward exciton manipulation for novel device applications.